Le Maghreb dans le système régional et international : crises et mutations - Amrani, Saâd; Lairini, Najib (Études internationales, 1991)
As the 1980s drew to a close in the Maghreb, old plans for unification were dusted off with the creation of the Arab Maghreb Union (UMA), an organization bringing together all five countries of North Africa : Algeria, Mauritania, Morocco, Tunisia, and Libya. This article seeks to analyze this new dynamic of regional integration by emphasizing its significance, its characteristics, its scope, and its limits. We express the hypothesis according to which the process of the Maghreb 's integration has been set in motion largely by the crisis in the inter-Arab System. Above all else, it represents a response to the constraints implicit in the push towards European union.